(untitled) (Journal of Forensic Medicine & Toxicology, 2023)
Introduction:: When a doctor takes up a patient, his medico legal duty is automatically assigned. It is imperative to quantify interns’ level of awareness on this topic to find areas of improvement, to gauge what concepts in terms of proper documentation needs more focus in the development of that skill. Methods: A self-designed questionnaire with the use of Likert scale (a psychometric scale) and some open-ended questions assessing knowledge, attitude and current practices of interns about medico legal documentation was prepared. After its validation, the 188 consenting interns were given the pre training questionnaire to answer so that the lacunae of the existing practices could be identified. One day training on medico legal documentation was provided to them and after a month, they asked to answer the post training questionnaire. Result: On comparison of the mean scores of knowledge, attitude and practices before and after the training, we get the p value < 0.001 which is of significance. In the study t-value was high, which meant that the net difference between the pre and post test scores for each intern is large and is an evidence that the training was effective. Discussion: The study concluded that the training conducted showed the overall improvement in the knowledge and practices of the interns towards medico legal documentation. From our study, it was evident that an uniform or standardized documentation system is needed in our institution, which is to be achieved through the proper training of medical students.